The Concept of Humanist Education from an Islamic Perspective and Its Implementation in Modern Learning - Joko Supriyanto; Deden Hidayat (LP3M Pascasarjana STAI Ibnurusyd, 2025)
Humanist education emphasizes the holistic development of learners by recognizing their dignity, potential, and freedom as human beings. From an Islamic perspective, humanist education is deeply rooted in the values of tauhid, justice, compassion, and respect for human dignity (karāmah al-insāniyyah). Islam views humans as both servants (‘abd) and vicegerents (khalīfah) of God on earth, implying a balanced educational approach that nurtures intellectual, spiritual, emotional, and social dimensions. This study aims to explore the concept of humanist education within Islamic teachings and analyze its implementation in modern learning contexts. Using a qualitative library research method, the study examines classical and contemporary Islamic educational thought alongside modern pedagogical theories. The findings indicate that Islamic humanist education promotes learner-centered approaches, dialogical learning, critical thinking, and ethical character formation. Its implementation in modern learning can be realized through inclusive classroom practices, contextual learning, integration of moral values, and the use of technology that supports creativity and autonomy. This study contributes to the development of an educational paradigm that harmonizes Islamic values with contemporary educational demands, offering a relevant framework for humanizing education in the modern era.